The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0261828
|View full text |Cite
|
Sign up to set email alerts
|

“To obey or not to obey” - Medical students’ response towards professional dilemmas in a hierarchical and collectivist culture

Abstract: Background Clinical clerkship programme in medical schools were developed to provide students with direct interactions with patients and observe clinical teachers in practice. However, professional dilemmas are prone to occur due to the nature of experiential learning. Several studies across different cultures showed that medical students responded differently towards professional dilemma. Aims This study aims to explore how medical students respond to professional dilemmas occurred during their clinical cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…The FOG phenomena may take place differently in different settings. Yet, it could be more influential towards students in the current setting since they might have felt discouraged to speak up and instead prioritize their acceptance and connectedness in the learning environment [ 34 ]. It is necessary to provide psychological safety, encouragement for students to seek feedback, and clear expectations from the teachers in feedback dialogue and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The FOG phenomena may take place differently in different settings. Yet, it could be more influential towards students in the current setting since they might have felt discouraged to speak up and instead prioritize their acceptance and connectedness in the learning environment [ 34 ]. It is necessary to provide psychological safety, encouragement for students to seek feedback, and clear expectations from the teachers in feedback dialogue and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragement of such reflective inquiries by students is necessary as it would facilitate their learning and their ability to take advantage for their professional development, even from the negative role modelling [ 42 ]. Coming from a culture where uncertainty tends to be highly avoided, this study underscores the importance of a more teacher-driven, structured, longitudinal approach, providing clear guidance and guidelines for students, to conduct reflective practice and in seeking feedback from their mentors [ 12 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those behaviors require further identification of underlying problems, remediation and even case dismissal if necessary [ 22 ]. Furthermore, a study in a hierarchical and collectivist culture underscores the strong influence of the culture towards clinical year students’ responses when they encounter professional dilemma [ 23 ], showing that professionalism and professional identity formation are always contextual and should consider sociocultural backgrounds [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that moral distress contributed to lower quality of patient care, cynical attitudes [ 35 , 36 ], diminished empathy [ 37 ], and accumulated over time and led to new morally stressful dilemmas [ 34 ]. A responsive reporting system, authority figure, and follow-up mechanism were facilitators in acting on professionalism dilemmas [ 38 ].…”
Section: Discussionmentioning
confidence: 99%